Effect of immobilised cervical spine on oropharyngeal sealing pressure with Ambu AuraGain™ Supraglottic airway: A randomised crossover trial - Uthaman, Duraiyarassu (Indian J Anaesth, 2019)
BACKGROUND AND AIMS: Ambu(®) AuraGain™ laryngeal airway (AuraGain) is one of the newer supraglottic airway device introduced in 2014. Cervical spine stabilisation with hard cervical collar makes insertion of supraglottic airways and tracheal intubation difficult. This study was conducted to investigate whether the presence of a cervical collar affects the oropharyngeal sealing pressure (OSP) and fibreoptic view of the glottis (Brimacombe score) in airways secured with the AuraGain. METHODS: The study was a randomised crossover trial. Thirty five ASA 1-3 patients undergoing elective surgery under general anaesthesia were recruited for the study. In each patient AuraGain was inserted twice in a crossover manner once with and once without a hard cervical collar in situ, with the sequence of insertion randomised. During each insertion of AuraGain the OSP, fibreoptic view of the glottis, insertion parameters, ventilator data and complications were noted. RESULTS: The mean OSPs in both the groups were similar with no significant difference (29.6 ± 3.7 cmH(2)O without collar and 30.1 ± 3.1 cmH(2)O with collar [P = 0.310]). The fibreoptic view of glottis was also similar in both groups. The insertion with collar was more difficult than without collar. The number of attempts for successful insertion was same in both the groups. The time taken for appropriate placement of LMA was significantly prolonged in patients with collar. CONCLUSIONS: We conclude that the Ambu AuraGain can be used to provide effective ventilation in patients whose cervical spine is immobilised with a hard cervical collar.